Peran Televisi Lokal dalam Pembangunan Daerah di Provinsi Sulawesi Tenggara (Studi Analisis Isi terhadap Isu – Isu Pembangunan Daerah) - Zulfiah Larisu (Universitas Muhammadiyah Sidoarjo, 2017)
The purpose of this study is to examine the liputanof local television in Southeast Sulawesi related development issues by using content analysis method. The main question posed in this research is how the liputanin local television (TVRI Stasiun Sulawesi Tenggara and SINDOTV Kendari) and is there a difference between the two television in raising the issue of development. The study found that the issue of development has become an important issue in both local television. Then when seen issues raised, there is a difference between the two televisions in raising the issue of regional development. Although economic issues occupy a portion of the second highest in the television, but there is a difference in the next sequence. TVRI Stasiun Sulawesi Tenggara is putting social issues of economic and social environment as an issue is more prominent, while SindoTV Kendari more highlights economic issues and economic environment. The charge of development issues are also different between the two televisions. TVRI Stasiun Sulawesi Tenggara further highlights the problems of development progress, while SINDOTV Kendari more precisely place the barriers of development as a more prominent issues.